AB0748 Study of antinucleolar pattern sera in an autoimmunity laboratory: antigenic specificities and clinical association. (23rd January 2014) - Téllez, R.; Serrano, C.; Vegas, C.; Tramón, P.; Rodríguez, M. J.; Romero, F.; Sanchez, O.; Martínez, M. J.
Abstract : Background: Indirect ImmunoFluorescence (IIF) nucleolar pattern has a low prevalence, being usually associated with Systemic Sclerosis (SSc). Despite the increasing number of tools that help us to identify antigenic specificities many nucleolar sera are not yet well characterized. Objectives: Identify antigenic specificities of sera that exhibit nucleolar pattern by IIF using the current methods available in an Autoimmunity Laboratory and investigate clinical association. Methods: The study included sera that were sent to our Laboratory to test Antinuclear Antibodies (ANA) from Nov. 2010 to Dec. 2012. Sera were screened by IIF (HEp-2, INOVA®). Nucleolar sera were further studied by ANA ELISA, ENA ELISA and RNAPol-III ELISA (QUANTA Lite® INOVA), PMScl (either by ELiA® or Immunoblot -BlueDot. D-tek®-), Fibrilarin, Scl-70 and Ro (ELiA® IgG InmunoCap Phadia®). Anti Nor-90 antibodies were analized by an external Laboratory. Clinical data were collected by systematic review of patients' records. Results: Nucleolar pattern was found in 68 (0.64%) out of 10568 sera studied by IIF. Mean age: 56 years (SD ±15). Female:Male ratio 2.77. The most prevalent pattern was clumpy nucleolar associated with diffuse nucleoplasm (56%). 62% of sera exhibited negative chromatin. Clinical diagnostics were: 35% (24) Connective Tissue Disease (CTD), 22% (15) Liver diseases, 43% (29) Other clinical features (Other). Among CTD, SSc was the most frequent diagnosis (62%). In 72% of sera no antigenic specificities were found. RNAPol-III and Scl-70 were the most frequently specificities identified: 10% (7) and 9% (6), respectively. All antiRNAPol-III positive showed diiffuse nucleoplasm, 71% (5) exhibited speckled nucleoli and 71% (5) had negative chromatin. Among positive Scl-70 all exhibited diffuse nucleoplasm, 67% (4) showed clumpy nucleoli and 67% (4) had positive chromatin staining. Only antiScl-70 specificities were in all cases detected by both ANA and ENA ELISA. No antigenic specificities were found in the group Liver diseases. In the group CTD 62% (15) were found an antigenic specificity: 25% Scl-70 (6), 21% RNAPol-III (5), 12% PMscl (3) and 4% Fibrilarin (1). Among the group Other 14% (4) had an antigenic specificity: 7% RNAPol-III (2), 3% Fibrilarin (1) and 3% Nor-90 (1). Conclusions: Nucleolar pattern has low prevalence, frequently presenting a mixed IIF pattern. Despite the classical association of nucleolar pattern with CTD we describe a high prevalence among other clinical settings. There are a high percentage of nucleolar sera in which antigenic specificities have not been identified, specially gathered in Liver diseases' group. In our study there is a cohort of patients that have not currently a definitive CTD diagnosis but exhibit characteristic antigenic specificities. A follow up must be considered in these patients to track future clinical implications. This might confirm the importance of studying nucleolar sera despite the absence of a current clinical suspicion. References: Antibodies to fibrillarin, PM-Scl and RNA polimerasa III detected by ELISA assays in patients with systemic sclerosis. Villalta et al, 2010 Atlas of Hep-2 patterns. Third edition. A.R Bradwell, R.G Hughes. The Binding Site Ltd, 2007 Disclosure of Interest: None Declared